Replication Forks Stalled at Ultraviolet Lesions Are Rescued via RecA and RuvABC Protein-catalyzed Disintegration in Escherichia coli - Khan, Sharik R. (American Society for Biochemistry and Molecular Biology, 2012)
Ultraviolet (UV) irradiation is not known to induce chromosomal fragmentation in sublethal doses, and yet UV irradiation causes genetic instability and cancer, suggesting that chromosomes are fragmented. Here we show that UV irradiation induces fragmentation in sublethal doses, but the broken chromosomes are repaired or degraded by RecBCD; therefore, to observe full fragmentation, RecBCD enzyme needs to be inactivated. Using quantitative pulsed field gel electrophoresis and sensitive DNA synthesis measurements, we investigated the mechanisms of UV radiation-induced chromosomal fragmentation in recBC mutants, comparing five existing models of DNA damage-induced fragmentation. We found that fragmentation depends on active DNA synthesis before, but not after, UV irradiation. At low UV irradiation doses, fragmentation does not need excision repair or daughter strand gap repair. Fragmentation absolutely depends on both RecA-catalyzed homologous strand exchange and RuvABC-catalyzed Holliday junction resolution. Thus, chromosomes fragment when replication forks stall at UV lesions and regress, generating Holliday junctions. Remarkably, cells specifically utilize fork breakage to rescue stalled replication and avoid lethality.